Monitoring bladder compliance using end filling detrusor pressure: Clinical results and related factors - Jin-Yi Liao; Yi-Hao Lin; Ching-Chung Liang; Wu-Chiao Hsieh; She-Jane Lee; Ling-Hong Tseng (Elsevier, 2015)
Objective: To assess the clinical significance of low compliance bladder (LCB) in women with lower urinary tract symptoms. Materials and Methods: Medical records of 1490 women undergoing videourodynamic studies (VUSs) were reviewed. Comprehensive medical histories, physical examinations, bladder diaries, and results of multichannel VUS were analyzed. This study adopted an end filling detrusor pressure (EFP) greater than 20 cmH2O to define LCB. Results: Among the study patients (n = 1490), 9.1% were diagnosed with LCB using a cutoff value of 17.5 cmH2O, which had a sensitivity and specificity of 89% and 92.7%, respectively. Results of multivariate analysis indicated that age (p = 0.005), maximum cystometric capacity (MCC; p = 0.002), detrusor overactivity (DO; p = 0.001), pelvic organ prolapse (POP; p = 0.018), recurrent urinary tract infection (p = 0.001), and radical abdominal hysterectomy (RAH; p < 0.001) as independent prognostic factors. Furthermore, our study results indicate that the MCC, urinary tract infection, and a history of RAH have a positive correlation with LCB, whereas, age, POP, and DO have a negative correlation with LCB. Conclusion: Our idea using EFP (≥17.5 cmH2O) for screening women with LCB is feasible for clinical use.